Deciphering Turkey's geopolitical balancing and Anti-Westernism in its relations with Russia - Galip Dalay (Stiftung Wissenschaft und Politik (SWP), 2022)
The war in Ukraine is set to increase the pressure on Turkey's balancing policy, shed light on the role of anti-Westernism in Ankara-Moscow relations, and reshape Turkey's relations with Russia and the West. The balancing policy will face a less permissive environment. However, a rupture in Turkey-Russia relations is not to be expected. Given the prohibitive cost of a breakdown, Ankara will strive to maintain functional bilateral relations with Moscow. More broadly, despite the changed context, Turkey will continue to seek autonomy in its foreign and security policy. This quest precedes the balancing policy and was not driven solely by discontent with the West. It was also informed by Turkey's reading of the global order becoming more multipolar and less Western-centric. In spite of similarities in their narratives, the Turkish and Russian anti-Westernisms manifest themselves differently in policy terms. Finally, Russia's geopolitical revisionism is set to drive Turkey and the West relatively closer together in matters geopolitical and strategic, provided that Turkey's current blockage of Sweden and Finland's NATO membership bid is resolved in the not too distant future.
Keywords: 320